(untitled) (Journal of Medical & Health Sciences Review, 2025)
Heavy metal contamination of the aquatic environment had recently become a major concern for aquatic organisms as well as public health. The present study was conducted to assess antioxidant enzymes catalase (CAT) and peroxidase (Px) activity in response to heavy metals from various organs of Oreochromis niloticus. Samples of fish and water were collected from different sites of River Jehlum. Fish were dissected to obtain different organs, extracted organs were homogenized in phosphate buffer for enzyme assay and antioxidant activity was measured. Some physico-chemical parameters, including Temp, DO and pH were measured on-site, while others (Mg, Ca and CO2) were checked in the laboratory. Data was statistically analyzed with software STATISTIX by applying one-way ANOVA. After ANOVA, comparison of means was done through Tukey’s test. The results indicated significant bioaccumulation of heavy metals in the liver, kidney, gills, heart and muscles. The trend of metals at all sites was recorded as Zn > As > Hg > Pb > Cr. Result indicated significant bioaccumulation of heavy metals in the liver, kidney, gills, muscles and heart of O. niloticus. The catalase activity level was maximum in the liver of fish, while peroxidase activity was higher in the kidney as compared to other organs. Antioxidant activity was measured in the following order: liver > kidney > gills > heart > muscles. This study is helpful in understanding the effects of heavy metal accumulation in the aquatic ecosystem and identified potential solutions that could be helpful in reducing its negative impacts.